Re-appearance of the gregarious gastropod Dendropoma anguliferum (Vermetidae) on abrasion platforms in the Carmel coast (Northern Israel) - BARNEAH, ORIT; LIDOR-NAIM, MICHAL; TSADOK, RAMI; YAHEL, RUTH; KUSHMARO, ARIEL (Mediterranean Marine Science, 2024)
After three decades of sharp decline in the Dendropoma populations in Israel and genuine concern for their extinction, we affirm the re-appearance of the gregarious gastropod Dendropoma anguliferum on abrasion platforms in the Carmel coast (Northern Israel). A visual survey conducted during December 2020 and February 2021 along the rims of abrasion platforms in the Carmel coast area revealed 195 living clusters of live D. anguliferum. DNA sequences from tissue samples unambiguously supported the identity of our material as the Levantine Sea member D. anguliferum of the Dendropoma petraeum species complex, with 99- 100% identity to sequences obtained from D. anguliferum from Southern Lebanon.